Penentuan Prioritas Pembangunan Jalan di Kabupaten Bengkayang Menggunakan Integrasi Metode ROC dan SAW - Charley Orilya Grasselly Alfa Delfiny Hartoyo Uray; Candra Gudiato (Saturnus: Jurnal Teknologi dan Sistem Informasi, 2026)
Road infrastructure development is essential for supporting economic growth and improving agricultural product distribution in Bengkayang Regency, Indonesia. However, the process of determining priority locations is not yet supported by a computerized decision-making system, which may result in inefficient and inappropriate resource allocation. This study developed a Decision Support System (DSS) to assist decision-makers in identifying and prioritizing locations for road infrastructure development. The system integrates the Rank Order Centroid (ROC) and Simple Additive Weighting (SAW) methods. ROC was used to determine the weights of the evaluation criteria, while SAW was applied to rank 17 district alternatives based on their total priority scores. The analysis used data from the 2025 Semester I and Semester II Population Profiles and evaluated each district based on land area, population density, productive-age population, and number of households. The results showed that Jagoi Babang obtained the highest score of 0.85079, making it the main recommended district for road development. Black-box testing confirmed that the system operated properly and met all functional requirements. The proposed DSS offers a systematic and objective approach to support more effective, accurate, and data-driven infrastructure planning decisions.